2011
DOI: 10.1002/clen.201100118
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Metal Ions onto the Chemically Modified Agricultural Waste

Abstract: This paper discusses about the adsorption of metal ions such as Cu(II), Cd(II), Zn(II), and Ni(II) from aqueous solution by sulfuric acid treated cashew nut shell (STCNS). The adsorption process depends on the solution pH, adsorbent dose, contact time, initial metal ions concentration, and temperature. The adsorption kinetics was relatively fast and equilibrium was reached at 30 min. The adsorption equilibrium follows Langmuir adsorption isotherm model. The maximum adsorption capacity values of the modified ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…At high pH levels the functional group undergoes dissociation and the surface of the adsorbent is negatively charged . Therefore, the number of active sites is higher, and metal ions are attracted due to electrostatic interactions . It should be noted that with increasing pH the amount of hydroxyl anions also increases.…”
Section: Resultsmentioning
confidence: 99%
“…At high pH levels the functional group undergoes dissociation and the surface of the adsorbent is negatively charged . Therefore, the number of active sites is higher, and metal ions are attracted due to electrostatic interactions . It should be noted that with increasing pH the amount of hydroxyl anions also increases.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies concluded that cadmium remains non-biodegradable when ingested into living systems and its circulation through the ecosystem is indestructible (Mutlu et al 2012;Kumar et al 2011). Cadmium exposure happens primarily through ingestion and inhalation and once it enters into the bloodstream, the erythrocytes transport it and at the intracellular phase, cadmium is engrossed to a portion of protein (Godt et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most of the contaminants were in the MeOH n form after sorption. The mechanisms of metals interaction with the surface of the sorbent particles leading to their accumulation can be represented by the following reactions: (6) The mechanisms of heavy metals sorption demonstrate how the geochemical barrier based on the building refuse acts to prevent the migration of pollutants into deeper soils layers. However, it is necessary to bear in mind that soils are dynamic systems there are the processes of substance migration, such as aqueous solutions of organic components and inorganic compounds, continuously occur.…”
Section: Resultsmentioning
confidence: 99%
“…A choice of its components depends on pollutant properties and economic feasibility. At present, mining waste [3], organoclay [4], farm waste [5,6] have been proposed as basic materials for artificial geochemical barriers. However, the use of mineral part of the building refuse for that is of interest of soils tilling from heavy metals.…”
Section: Introductionmentioning
confidence: 99%